Professores das séries iniciais em início de carreira: dificuldades, dilemas e saberes em relação ao ensino da matemática - Silva, Silmara da (2009)
This research intended to deepen the discussions about the beginning of the teachers career, trying to comprehend how they face the situations that are presented in the school s quotidian while teaching Mathematics. The purpose of this study was to understand the difficulties, the challenges and the knowledge of the teachers that teach Mathematics in the first grades in the beginning of their career. The subjects of the research were teachers of initial grades within 5 years of experience, from the private and public network of a city in the state of São Paulo. The data were collected by means of intensive interviews and video recordings. The theoretical referential that served as a basis for this research, involves three axes: beginning of the career, difficulties, challenges and teacher s knowledge. In the process of data analysis, the following categories were privileged: entrée in career, classroom practice, support, school context, teacher s conception and difficulties in relation to education. The studies result showed that some teachers present difficulties while teaching certain contents and not remembering the Mathematics content or the didactic of teaching Math studied at the Didactics course or at teacher training. The teachers point, also, the students indiscipline as a difficulty faced as a challenge for the teachers beginning their careers. Another important finding is in relation to professional development, most worry about taking courses to improve their classroom practice. The lack of support by managers, co-workers and parents was highlighted as one of the aspects that have direct connection with the difficulties faced by the teachers in this career phase and might be an alert to the own teaching system and to the school institutions about their responsibility in relation to this aspect